Soil, Water and Land Use: III. Wetlands - Nancy Johnson (EDIS)
The goal of Soil Water and Land Use: III. Wetlands is to enhance the understanding of wetlands — from their uniqueness as ecosystems to their benefits for humans. The conservation and restoration of wetlands is often an emotive issue. Through better understanding of wetlands, students will be able to make more responsible and informed decisions about these natural resources. This information was produced jointly by the Soil and Water Science Department and the 4-H Youth Development Program. Published March 2002 as SPESL42 and 4HESL42, Florida Cooperative Extension Service. Reviewed March 2002. Printed March 2002.